A subversive gospel : Flannery O'Connor and the reimagining of beauty, goodness, and truth - Bruner, Michael Mears, 1965- (Studies in theology and the arts., 2017)
The good news of Jesus Christ is a subversive gospel, and following Jesus is a subversive act. Exploring the theological aesthetic of American author Flannery O'Connor, Michael Bruner argues that her fiction reveals what discipleship to Jesus Christ entails by subverting the traditional understandings of beauty, truth, and goodness.